2020
DOI: 10.1111/jog.14228
|View full text |Cite
|
Sign up to set email alerts
|

Robotic surgery for gynecologic cancers: indications, techniques and controversies

Abstract: Minimally invasive surgery for gynecologic cancers is associated with fewer postoperative complications including less blood loss and quicker recovery time compared to traditional laparotomy. The robotic platform has allowed patients access to minimally invasive surgery due to its increased utilization by gynecologic oncologists. Many surgeons have embraced the robotic platform due to its technological advances over traditional laparoscopy including high-definition 3D optics, wristed instrumentation, camera st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Robot-assisted surgery is very important for gynecologic malignancies because, like prostate cancer surgery, it requires delicate deep-field techniques and good visualization. Moreover, robot-assisted surgery is also indicated for benign uterine myoma, and in the United States, the gynecological department comprised the largest number of robot-assisted surgery [3,4]. Some papers have reported that the learning curve for robotassisted surgery requires 20 to 30 cases for significant improvement in many departments, including gynecology and urology [5][6][7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Robot-assisted surgery is very important for gynecologic malignancies because, like prostate cancer surgery, it requires delicate deep-field techniques and good visualization. Moreover, robot-assisted surgery is also indicated for benign uterine myoma, and in the United States, the gynecological department comprised the largest number of robot-assisted surgery [3,4]. Some papers have reported that the learning curve for robotassisted surgery requires 20 to 30 cases for significant improvement in many departments, including gynecology and urology [5][6][7].…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is one of the factors complicating cancer surgery due to the obstruction of surgical view by adipose tissues, especially for open surgeries. The implementation of robotassisted surgery was found to overcome this issue in obese patients because it does not require as much force to operate forceps or secure visual fields [4,5]. Another study reported that in obese patients, robot-assisted surgery was associated with a significantly reduced operating time and blood loss, increased number of lymph nodes removed and decreased hospital stay compared with open surgery [4].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More In the current literature, there is no reliable scoring system that can predict duration or difficulty of open abdominal, laparoscopic or robotic-assisted laparoscopic procedures. 8,9 For this reason, in our plans is to organise a multicentre retrospective or prospective trial to clarify the possible predictive value of our proposed Iavazzo score in all gynaecological procedures performed robotically and compared them with analysis in open and laparoscopic approach.…”
Section: F I G U R E 1 Correlation Between 'Iavazzo Score' and 'Surge...mentioning
confidence: 99%
“…In the challenge of preserving healthy tissues next to the tumor, radiation oncologists can irradiate target cells while preserving surrounding areas to avoid long-term toxicity [24]. Roboticassisted surgery is likely to help surgeons manage patients with high BMI with a minimally invasive approach (meaning shorter hospitalization and less pain) [25]. Personalized treatments can also be integrated with alternative approaches (e.g., palliative and supportive care) to provide the relief of cancer-related symptoms in the end-of-life setting.…”
Section: Physiological and Safety Needsmentioning
confidence: 99%